An Alternative Algorithm for Optimal Design of Plate Heat Exchangers. (February 2015) - Javid, Seyyed Morteza; Farshidianfar, Anoushiravan; Golparvar, Seyyed Behzad
Due to the complex geometry of plate heat exchangers and thus a large number of variables affecting the performance of the exchangers, the design of these types of exchangers is quiet difficult. However, unlike the shell and tube heat exchangers which contain available data of design procedures, the design of plate heat exchanger is a monopoly of some certain manufacturing companies that make the problem even worse. In this paper, the objective is to minimize the number of plates in plate heat exchanger; in order to achieve that, a simple and yet efficient mathematical model is introduced for determination of the pressure drop and heat capacity of a plate heat exchanger in single- and multipass state and also a program was defined for determination of optimal solution based on this simple mathematical model for given operational constraints and plate type. In the end, the optimal solution will be compared to the answer of CAS200 commercial software and also it is shown that the effect of the start and end plates and transverse distribution in optimal solution is considerable.